Multi-Actor Governance in Stunting Reduction A Qualitative Study with Contextual Validation in East Jakarta - Hendra Asep; Muhammad Rahimi Hasan (Department of Public Administration, 2026)
This study examines how collaborative governance operates in the implementation of stunting reduction policies in Indonesia by integrating the perspectives of collaborative governance and the Penta-Helix model. It aims to identify the dominant governance patterns found in national empirical studies and to examine how these patterns are reflected in the governance practices of East Jakarta. A qualitative research design was applied through a two-stage approach. The first stage involved bibliometric analysis and a systematic literature review of national studies on collaborative governance and stunting reduction, followed by thematic coding to identify key governance dimensions. The second stage consisted of contextual validation through interviews with key stakeholders and analysis of policy documents related to stunting governance in East Jakarta. The findings show that national studies mainly emphasize actor configuration, especially the distribution of roles among government institutions, private sector actors, communities, and media stakeholders. Governance processes, such as leadership coordination and multi-level planning, are also important in sustaining collaboration, while institutional mechanisms, including monitoring systems and data coordination, receive less attention in the literature. Empirical evidence from East Jakarta indicates that the local government acts as a central integrator, coordinating multi-actor participation through institutional platforms and policy coordination mechanisms. The interaction among actor configuration, governance processes, and institutional mechanisms shapes the operational structure of collaborative stunting governance. Based on these findings, the study proposes an integrated governance framework that emphasizes alignment among actor participation, coordination processes, and institutional support. It recommends strengthening institutional coordination, improving cross-sector data integration, and increasing the role of non-government actors to support sustainable stunting reduction initiatives.